2004
DOI: 10.1021/nl0496567
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Nanostructured Polymeric Surfaces for Biosensing Devices

Abstract: In this paper a method for fabricating nanostructured polymeric surfaces with contrasted chemical functionality is presented. First, a polymer film of acrylic acid (PAA) is deposited by plasma enhanced chemical vapor deposition. It is covered by a monolayer of particles in the 500 nm range. Then oxygen plasma etching is performed, providing etching of both nanoparticles and acrylic acid film present between the masks. The etching process is stopped before the complete etching of the nanoparticles and the resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 6 publications
1
77
0
Order By: Relevance
“…As compared with convention- Updates in Advanced Lithographyally used polymer masks such as photoresists removed by organic developers, colloidal masks can be removed easily by ultrasonication and thus cause less damage to nanostructured substrates obtained via RIE. Ordered arrays of polyacrylic acid domes have been fabricated by using 2D PS colloidal crystals as masks for O 2 RIE of the polymeric films; the removal of the PS masks has no damage to the surface chemistry and the structure of the resulting polymeric domes, thus enabling conjugation of proteins [55]. 2D PS colloidal crystals have been also used as masks for dry etching of SiO 2 slides to create periodic arrays of nanoplates, which can be transferred onto polymer films by imprinting [56].…”
Section: Controllable Etchingmentioning
confidence: 99%
See 1 more Smart Citation
“…As compared with convention- Updates in Advanced Lithographyally used polymer masks such as photoresists removed by organic developers, colloidal masks can be removed easily by ultrasonication and thus cause less damage to nanostructured substrates obtained via RIE. Ordered arrays of polyacrylic acid domes have been fabricated by using 2D PS colloidal crystals as masks for O 2 RIE of the polymeric films; the removal of the PS masks has no damage to the surface chemistry and the structure of the resulting polymeric domes, thus enabling conjugation of proteins [55]. 2D PS colloidal crystals have been also used as masks for dry etching of SiO 2 slides to create periodic arrays of nanoplates, which can be transferred onto polymer films by imprinting [56].…”
Section: Controllable Etchingmentioning
confidence: 99%
“…Mulvaney's group has grown monolayer and multilayer films of semiconductor quantum dots on surface patterns derived from NSL, leading to nanostructured luminescent thin films [90,91]. Valsesia et al have used ordered arrays of polyacrylic acid domes derived via NSL to selectively couple with bovine serum albumin [55]. Using NSL-derived surface patterns as templates to grow proteins, Sutherland et al have found that the surface topography enhances the binding selectivity of fibrinogens to platelets [92].…”
Section: Extension Of Colloidal Lithographymentioning
confidence: 99%
“…The deposition process of the plasma polymerized PEO-like and PAA films are described in details elsewhere [32,44,45,39]. Briefly, the systems used are capacitively coupled reactors with two symmetrical parallel-plate electrodes.…”
Section: Plasma Polymerisation Of Functional Filmsmentioning
confidence: 99%
“…Due to their variable degree of cross-linking linked to the discharge conditions, these coatings are resistant to classical polar solvents, making them compatible with almost all standard patterning techniques including lift-off processes [39,40,41], but can also be selectively dissolved upon request. Plasma polymers can be then assembled in structures with sub-micron dimensions by combination of colloidal lithography [39,44], deposition and etching, or as well as by direct modifications by electron beam lithography.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation